2009
DOI: 10.1080/10656210902751826
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Biblical Literacy, Academic Achievement, and School Behavior Among Christian- and Public-School Students

Abstract: This study assessed the relationship between Bible literacy among secondary school students and their academic achievement and school behavior. A total of 160 students who attended either Christian or public schools in the 7th to 12th grade were randomly selected for the study sample. Three measures of Bible knowledge were combined to obtain an overall measure of Bible literacy. The results indicate that students with the highest level of Bible literacy also had the highest average grade point average (GPA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…A separate cross-country study also showed that students from private schools obtained higher scores in mathematics, reading and science than those from public schools [21]. Students from Pacelli School outperforming students from Onitolo on knowledge questions on cause of malaria agrees with other studies that find higher academic achievements among private, Christian schools [20,21].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A separate cross-country study also showed that students from private schools obtained higher scores in mathematics, reading and science than those from public schools [21]. Students from Pacelli School outperforming students from Onitolo on knowledge questions on cause of malaria agrees with other studies that find higher academic achievements among private, Christian schools [20,21].…”
Section: Discussionsupporting
confidence: 75%
“…A study on the relationship between bible literacy and academic achievements among students attending public schools and students attending Christian schools showed that those that had higher scores on Bible literacy had higher academic achievements [20]. A separate cross-country study also showed that students from private schools obtained higher scores in mathematics, reading and science than those from public schools [21].…”
Section: Discussionmentioning
confidence: 99%
“…Christian school students and public school students and found no statistically significant difference between the two groups in regards to school moral behavior (Jeynes, 2009). …”
Section: Vlllmentioning
confidence: 99%
“…Many of the early American colonists came to the New World with the desire to practice their religious and moral beli efs (Algera & Sink, 2002). lJ1itially, religious education was the primary purpose for early American schools, and these schools were under the control of the community churches (Passe & Willox, 2009 (Jeynes, 2009;Watson, 2010;Vhight, 1999). These events helped lead to the secularization of public schools; and, as a result, there was a move for the privati za tion of religious, Christian schools (\Vatson, 201 0).…”
Section: History Of Religious Education and Private Christian Schoolsmentioning
confidence: 99%
See 1 more Smart Citation